PRINSIP MANAJEMEN PERSPEKTIF PENDIDIKAN ISLAM - Dwi Faruqi; Lutfy Hakim (Roqooba Journal of Islamic Education Management, 2022)
Islamic education management always need a suitable new inovation with currebt development, so it can give more benefits. Islamic education system is a system that make Qur’an and Hadist as main resource which teach and guide people to get a better life in the world and hereafter. Madrasah as education organization has to adapt with global culture development, include management knowledge. Madrasah must implemented the management principles of islamic education in the organization that it manages. Base princip of islamiceducation which must to be considered to get the aim is implication and people characteristics, integrate, balance, universal and dynamic. Management principles of islamic education are include planning, organizing, giving mandate to profesional, appreciation, conflict management, and consistent.